Kajian Literatur Perilaku People Pleaser pada Siswa - Salsabila Nuri Aziza; Itsna Iftayani; Aufa Angga Wimaswara (Yayasan Literasi Sains Indonesia, 2026)
People pleaser behavior among students is an important topic in educational psychology, as it is closely related to mental and emotional balance during adolescene. This study aims to identify and analyze the factors contributing to people pleaser behavior among secondary school students in Indonesia. The reserch employed a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Data were collected from there major databases-Google Scholar, Crossref, and OpenAlex-with a publication range from 2021 to 2025. Out of 1.235 articles identified, six met the inclusion and exclusion criteria. The findings show that people pleaser behavior in influenced by internal and external factors. Internal factors include fear or rejection, low self confidence, high social approval needs, and weak assertiveness. External factors consist of academic pressure, family expectations, peer influence, and school environments emphasizing conformity. The interaction of these factors contributes to stress, anxiety, and decreased students well-being. This study highlights the importance of implementing assertive counseling programs, strengthening self-concept, and fostering family and school support to help students balance social empathy and personal mental health.